Study of effect of Nigella sativa on prevention of nephrotoxicity induced by colistin in experimental animals - Rana, M. Azmat; Arshad, M. Nadeem; Siddiqui, Salman Shafi; Nasiruddin, M. (International Journal of Basic & Clinical Pharmacology, 2019)
ABSTRACT Background: Nigella sativa, a widely used medicinal plant throughout the world belongs to family ranunculaceae. Its Seeds and oil have a long history of folklore usage in various traditional systems of medicines and food. This study was performed to evaluate the protective effect of Nigella sativa oil (NSO) on kidney when simultaneously given with colistin sulfate (CS) which induces tubular damage in rats. Methods: Animals were treated for 7 days: Group I (n=6) with normal saline and CMC, Group II, III and IV with 300.000IU/kg/day of CS (n=6). Group III and Group IV with NSO at the dose of 1 and 2ml/kg per orum prior to CS administration. All the animals were sacrificed on 8th day. Afterwards, the plasma creatinine (pCr), blood urea, renal tissue level of malondialdehyde (MDA), reduced glutathione (GSH) and renal histology were performed. Results: Colistin sulfate induced tubular damage, increased the plasma creatinine (pCr), blood urea and MDA levels and decreased the reduced glutathione (GSH). However, simultaneous treatment with Nigella sativa oil at the dose of 1ml/kg and 2ml/kg for one week produced dose dependant improvement in tubular damage and reduced the biochemical alteration. Conclusions: It could be concluded that, Colistin sulfate induced nephrotoxicity is ameliorated by NS oil especially in higher dose of (2ml/kg). This nephroprotective effect is ascribed to free radical scavenging and potent antioxidant activity in Nigella sativa.